OPTIMIZATION OF BACTERIOCIN PRODUCTION BY Lactococcus lactis ssp. lactis CN1.10a ORIGIN FROM RUSIPS - Ninoek Indriati; Arifah Kusmarwati; Irma Hermana (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2014)
Previous study of bacteriocin production on laboratory scale (100 mL) that used MRS broth medium produced unstable activity of bacteriocin. Therefore, this study aims to determine the optimum growth conditions and media for production of bacteriocin. Bacteria used in this research was a lactic acid bacteria (LAB) Lactococcus lactis ssp. lactis CN1.10a  isolated from rusip, a traditional Bangkanese fermented fish product.The bacteria was first cultivated for subsequent use of bacteriocins production on intermediate scale (2L). Followed by the optimization of temperature, pH and medium for the bacteriocin production, determination of cell growth curve, bacteriocin production curve, bacteriocin activity on that scale, and also stability of bacteriocin during storage.The results showed that the optimum temperature and pH for the growth of producer cell were 28°C and pH 6. The greatest activity of bacteriocin was produced on CM medium (1% sucrose, 0,45% peptone, 1% yeast extract, 2,84% KH2PO4, 0,2% NaCl and 0,02% MgSO4.7H20) in addition of sucrose as carbohydrate source. Based on the growth curve performedon CM medium with KH2PO4, the L. Lactis ssp lactis CN1.10a was relatively stable up to 48 hours. Bacteriocin produced by the cell was  8000 AU/mlat24th hour.Bacteriocin  was relatively stable when stored at -20°C for 1month with a relative activity of 69,4%.